2002
DOI: 10.1007/s10270-002-0008-4
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Unified Modeling Language for ontology development

Abstract: There is rapidly growing momentum for web enabled agents that reason about and dynamically integrate the appropriate knowledge and services at runtime. The dynamic integration of knowledge and services depends on the existence of explicit declarative semantic models (ontologies). We have been building tools for ontology development based on the Unified Modeling Language (UML). This allows the many mature UML tools, models and expertise to be applied to knowledge representation systems, not only for visualizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 14 publications
0
57
0
2
Order By: Relevance
“…We realised the limitations of UML for ontology development (Baclawski et al, 2002), (Gómez Pérez et al, 2004b), (Gasevic et al, 2006b). Our decisión was based on the fact that our review of ontologies for autonomous systems and software engineering showed the wide use of UML to specify such ontologies (Gasevic et al, 2006a), (Tamma et al, 2005), (Ruiz and Hilera, 2006).…”
Section: Oasys Featuresmentioning
confidence: 99%
“…We realised the limitations of UML for ontology development (Baclawski et al, 2002), (Gómez Pérez et al, 2004b), (Gasevic et al, 2006b). Our decisión was based on the fact that our review of ontologies for autonomous systems and software engineering showed the wide use of UML to specify such ontologies (Gasevic et al, 2006a), (Tamma et al, 2005), (Ruiz and Hilera, 2006).…”
Section: Oasys Featuresmentioning
confidence: 99%
“…Though the semantics of a model is structurally defined by its meta-model, the mechanisms to describe the semantics of the domain are rather limited compared to knowledge representation languages. In addition, MDA-based languages do not have a knowledge-based foundation to enable reasoning (e.g., for supporting QA) [2]. System integration can benefit from the integration with ontology languages such as RDF and OWL [9,10] in various ways, e.g., by reducing language ambiguity, enabling validation and automated consistency checking.…”
Section: Ontologies For Semantic Integrationmentioning
confidence: 99%
“…However, although the semantics of a model are structurally defined by its metamodel, these mechanisms to describe the semantics of the domain are rather limited compared to knowledge representation languages. In addition, MDA-based languages do not have a knowledge-based foundation to enable reasoning [1]. Software modeling languages and methodologies can benefit from the integration with ontology languages such as RDF and OWL, e.g., by reducing language ambiguity, enabling validation, and automated consistency checking.…”
Section: Use Of Ontology In Software Engineeringmentioning
confidence: 99%
“…There are reports on using ontologies for software engineering: a) for describing the problem domain; b) for the semantic description of transformations between models in Model-Driven Development (MDD); and c) for QA reasoning on semantic inconsistencies between models [1]. However, we found very little work on ontologies to provide a continuous model for linking different stages of the engineering process of softwareintensive systems.…”
Section: Introductionmentioning
confidence: 98%